Development of Handouts on Redox Material to Improve the Students Cognitive Abilities Using the Sorogan-Bandongan Learning Model - Nur Ainun; Rinaningsih Rinaningsih (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The Sorogan-Bandongan learning model is a traditional approach to enhancing students’ cognitive abilities through a structured series of activities, including diagnostic testing, independent practice, and self-reflection. This model effectively bridges student-centered individual learning (Sorogan) with collective discussion and evaluation (Bandongan), fostering both personal responsibility and collaborative engagement. This Research and Development (R&D) study, employing Thiagrajan's 4D model (Define, Design, Develop, Disseminate) through the development stage, aims to evaluate the feasibility of a chemistry handout on redox reactions based on this model. The feasibility was assessed through three main criteria: validity, practicality, and effectiveness. Analysis of the research instruments revealed that the handout is highly qualified across all parameters. In terms of validity, both content and construct aspects received a mode score of 4, placing them in the